Convalescent Memory T Cell Immunity in Individuals with Mild or Asymptomatic SARS-CoV-2 Infection May Result from an Evolutionarily Adapted Immune Response to Coronavirus and the 'Common Cold' - Stefano, George B; Kream, Richard M (Medical Science Monitor, 2020)
Recent studies have shown a significant level of T cell immunity to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in convalescent coronavirus disease 2019 (COVID-19) patients and unexposed healthy individuals. Also, SARS-CoV-2-reactive T memory cells occur in unexposed healthy individuals from endemic coronaviruses that cause the 'common cold.' The finding of the expression of adaptive SARS-CoV-2-reactive T memory cells in unexposed healthy individuals may be due to multiple cross-reactive viral protein targets following previous exposure to endemic human coronavirus infections. The opinion of the authors is that determination of protein sequence homologies across seemingly disparate viral protein libraries may provide epitope-matching data that link SARS-CoV-2-reactive T memory cell signatures to prior administration of cross-reacting vaccines to common viral pathogens. Exposure to SARS-CoV-2 initiates diverse cellular immune responses, including the associated 'cytokine storm'. Therefore, it is possible that the intact virus possesses a required degree of conformational matching, or stereoselectivity, to effectively target its receptor on multiple cell types. Therefore, conformational matching may be viewed as an evolving mechanism of viral infection and viral replication by an evolutionary modification of the angiotensin-converting enzyme 2 (ACE2) receptor required for SARS-CoV-2 binding and host cell entry. The authors propose that convalescent memory T cell immunity in individuals with mild or asymptomatic SARS-CoV-2 infection may result from an evolutionarily adapted immune response to coronavirus and the 'common cold'.
Keywords: Virus Internalization; Cross Reactions; imunologická paměť; T-Lymphocyte Subsets; Epitopes, T-Lymphocyte; protilátky virové; Immunologic Memory; zkřížené reakce; replikace viru; virové proteiny; Sequence Homology; epitopy T-lymfocytární; Angiotensin-Converting Enzyme 2; Rhinovirus; Common Cold; molekulární evoluce; Evolution, Molecular; T-lymfocyty - podskupiny; internalizace viru; nachlazení; sekvenční homologie; SARS-CoV-2; T-lymfocyty; Severity of Illness Index; Viral Proteins; angiotensin-konvertující enzym 2; Viral Vaccines; lidé; buněčná imunita; asymptomatické infekce; Virus Replication; Humans; Immunity, Cellular; Antibodies, Viral; Asymptomatic Infections; T-Lymphocytes; stupeň závažnosti nemoci; Immunogenicity, Vaccine; virové vakcíny; imunogenicita vakcíny; COVID-19